Cardiac-specific overexpression of metallothionein attenuates myocardial remodeling and contractile dysfunction in l-NAME-induced experimental hypertension: Role of autophagy regulation. Issue 2 (2nd September 2015) - Yang, Lifang; Gao, Jian-Yuan; Ma, Jipeng; Xu, Xihui; Wang, Qiurong; Xiong, Lize; Yang, Jian; Ren, Jun
Highlights We examined the impact of l-NAME-induced hypertension on cardiac responses. l-NAME challenge altered cardiac morphology, function and autophagy. Metallothionein alleviated l-NAME-induced anomalies in cardiac structure and function. The beneficial effect of metallothionein may be mediated through restored autophagy.